Popular naming for goods and materials in the Iraqi slang "A Semantic Study" (Journal of the College of Education for Women, 2019)
The current research is concerned with the prices of Goods and materials in the Iraqi slang a descriptive, lexicographic , and semantic study expressing the meanings of these names and their positions , as well as expressing the imaginations of Human mind , the popular mind in describing these goods with evaluating them besides the semantic of each word accordinglyThe current research is divided into two parts , the first part is consisted of Vocalizations" words" That are arisen through cognitive naming that concentrate on the mental imaginations for the most important and sensitive such as colors , taste , shapes and forms impacts of Goods and materials according to users' ' taste for those words , on other hand, the second part of research is concerned with those words that are emerged from the mechanism of expressing naming thst concentrates on a social and psychological evaluation for those goods through the semantic and marginal significance that express the Goods with the semantic points or in according to Guess within the mechanism of Modulated semantic.